2020
DOI: 10.1007/s10071-020-01409-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shared information and owner behavior on showing in dogs (Canis familiaris)

Abstract: Dogs’ production of referential communicative signals, i.e., showing , has gained increasing scientific interest over the last years. In this paper, we investigate whether shared information about the present and the past affects success and form of dog–human interactions. Second, in the context of showing, owners have always been treated as passive receivers of the dog’s signals. Therefore, we examined whether the owner’s behavior can influence the success and form of their dog’s showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 88 publications
2
10
0
Order By: Relevance
“…"/"where is the food?"). This result is in line with that reported by Henschel et al (2020). They found that dogs' showing behavior was disrupted by owners' requests to show where a hidden toy was located.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…"/"where is the food?"). This result is in line with that reported by Henschel et al (2020). They found that dogs' showing behavior was disrupted by owners' requests to show where a hidden toy was located.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, dogs engaged in showing behavior when the target was a dog-toy, but not when it was an object the person was interested in: however, when both objects were irrelevant to the dogs, but one was needed by the human partner, they gazed longer at the relevant one in trials including vocal communication (i.e., the experimenter talked to them in a high-pitched voice while searching), compared to silent trials (Piotti and Kaminski 2016 ). Finally, Henschel et al ( 2020 ) found that dogs’ showing success was negatively influenced by their owner’s behavior, as the more the owners pushed them to show where a hidden toy was, the less accurate dogs were. Taken together, these studies indicate that the out of reach/hidden object task is a valid experimental procedure to test dogs’ production of communicative signals and has ecological validity, because dogs live in a human environment and regularly face similar situations throughout their lives.…”
Section: Introductionmentioning
confidence: 99%
“…One might argue that the inattentiveness of the owner could have limited the communicative performance of the subjects. Indeed, visual contact with and visual reassurance from the human partner are known to increase animals’ human-oriented communication 19 , 60 . In the current study, we decided on an inattentive owner to prevent his/her behaviour from influencing the animals’ spontaneous communicative pattern.…”
Section: Discussionmentioning
confidence: 99%
“…In support, almost all domestic species tested so far exhibit referential communicative behaviours towards humans 9 11 , 17 , 18 . Remarkably, however, all species for which referential communication with humans has been reported (dogs 17 , 19 , goats 9 , 20 horses 10 , 21 , cats 18 , dolphins 12 , wolves 22 , kangaroos 15 , non-human primates 8 , 13 ) use visual social signals efficiently and rely on them heavily for within-species communication and cooperation. This raises the alternative hypothesis that readiness for human-oriented referential communication may not emerge in species that lack certain species-specific characteristics such as the efficiency of intraspecific visual communication.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when dogs are confronted with an unsolvable problem, they look back to their owners to elicit help 22 , 23 . Similarly, dogs indicate the location of food or toys to their owners when owners have not seen where these rewards were hidden 24 26 . Sometimes they even show the location of objects in which they are not interested in (i.e.…”
Section: Introductionmentioning
confidence: 99%